Characterizing galaxy clusters by their gravitational potential: systematics of cluster potential reconstruction - Tchernin, Céline; Lau, Erwin T.; Stapelberg, Sebastian; Hug, Damaris; Bartelmann, Matthias (Astronomy and astrophysics, 2020)
Biases in mass measurements of galaxy clusters are one of the major limiting systematics in constraining cosmology with clusters. We aim to demonstrate that the systematics associated with cluster gravitational potentials are smaller than the hydrostatic mass bias and that cluster potentials could therefore be a good alternative to cluster masses in cosmological studies. Using cosmological simulations of galaxy clusters, we compute the biases in the hydrostatic mass (HE mass) and those in the gravitational potential, reconstructed from measurements at X-ray and millimeter wavelengths. In particular, we investigate the effects of the presence of substructures and of nonthermal pressure support on both the HE mass and the reconstructed potential. We find that the bias in the reconstructed potential (6%) is less than that of the HE mass (13%) and that the scatter in the reconstructed potential decreases by ∼35% with respect to that in the HE mass. This study shows that characterizing galaxy clusters by their gravitational potential is a promising alternative to using cluster masses in cluster cosmology.
Gesehen am 15.02.2022